La cárcel en Colombia : espacio para la venganza y la reincidencia - Ossa López, María Fernanda (Medellín, Colombia : Ediciones UNAULA, 2016)
Analyzes recidivism in Colombia on the basis of a survey of 102 female inmates of the Centro Carcelario y Penitenciario El Pedregal of Medellín, Colombia. The study reflects the current situation of prisons and the difficult socio-economic and cultural conditions that lead people to seek out crime as a solution.
Based on the author's thesis (master's)--Universidad de Medellín.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed April 6, 2018)
Keywords: Prisons -- Colombia; Recidivism -- Colombia; Crime -- Colombia; Colombia -- Social conditions -- 1970-; Recidivists -- Colombia; Women prisoners -- Colombia; Electronic books